A case study of the space planning of ALS classrooms in a public high school in Quezon City in the application of the program's learning strands - Abrenilla, Keeza Jazztyn S.
The study examined the space planning of ALS classrooms in a public high school in Quezon City in the application of the program's learning strands. Lack of funding resulted in restriction of resources and activities being conducted. However, space planning is still crucial for the learning strands' activities to be executed. Purposive sampling was used to choose the location where it was required to be a public high school with ALS, and was located within Quezon City. Twelve of the respondents for the survey were chosen through convenience sampling where they were enrolled under ALS in the chosen public high school in Quezon City. Two to three weeks were spent on data collection. Tools used were ocular observation, photo documentation, survey questionnaires, focus discussion and interview. The study showed that in the chosen Alternative Learning System classroom, it was not able to fully apply all five learning strands in space planning. Table group layout was the frequently used layout during individual exercises. Correa et al. (2017) discussed that the table group layout was not best used for individual activities due to distractions. This was further validated when students did not rank the layout highest for individual activities. Findings showed that existing issues were observed to which the users have adapted to Users stated that this was not an issue, but Weinstein (1977) explained that compatibility of the physical and curriculum is essential for effective learning. The researcher recommended that longer period of the study should be conducted. In addition, DepEd and professional interior designers are recommended to use the study in creating standardized designs fit for ALS classrooms and the program's learning strands.